----------------------------------------------------
Define the numbers
----------------------------------------------------
Let the first even number be x
1st even number = x
2nd even number = x + 2
3rd even number = x + 4
----------------------------------------------------
Form the equation and solve
----------------------------------------------------
x + x + 2 + x + 4 = -6
3x + 6 = -6
3x = - 12
x = -4
----------------------------------------------------
Find the numbers
----------------------------------------------------
1st even number = x = -4
2nd even number = x + 2 = -4 + 2 = -2
3rd even number = x + 4 = -4 + 4 = 0
----------------------------------------------------
Answers: The numbers are -4, -2 and 0